AFC1 Compound Attenuated MI/R-Induced Ventricular Remodeling via Inhibiting PDGFR and STAT Pathway - Liu, Jie; Zhou, Xiaohui; Meng, Qingshu; Huang, Kevin W.; Liu, Jing; Tie, Jinjun; Zhuang, Rulin; Chen, Guohan; Zhang, Yuhui; Wei, Lu; Huang, Li; Li, Chun Guang; et al. (Frontiers in Pharmacology, 2019)
Effective interventions to improve the outcome of patients subjected to myocardial ischemia reperfusion(MI/R) are urgent in clinical settings. Tanshinone IIA(TSA) is reported to attenuate myocardial injury and improve ventricular remodeling post MI/R. Here, we evaluated the efficacy of AFC1 compound that was derived by modifying TSA structure in murine MI/R models. We found that AFC1 had a comparable effect of improving murine cardiac function after MI/R while it was superior to TSA in safety profile. Administration of AFC1 reduced reactive oxygen species (ROS) production, inflammatory cells infiltration and the expression of platelet derived growth factor receptors (PDGFR) in infarcted myocardium. Treatment with AFC1 also attenuated MI/R-induced cardiac remodeling and contributed to the recovery of cardiac function. Additionally, AFC1 reversed the elevation of PDGFR expression induced by PDGF-AB in both NCMs and NCFs and suppressed PDGF-AB induced NCM hypertrophy via STAT3 pathway and NCF collagen synthesis through p38-MAPK signaling in vitro. Similarly, AFC1 may contribute to the recovery of cardiac function in mice post MI/R via suppressing STAT signaling. Our results confirmed that AFC1 exerts anti-hypertrophic and anti-fibrotic effects against MI/R-induced cardiac remodeling, and suggest that AFC1 may have a promising potential in improving the outcome of patients suffered MI/R.